Potret Perempuan di Dunia Kuno dan di Injil Yohanes - Lassa, Nofida Fitria (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract. The author highlights that there is still a lot of discriminative action against women, even in the church environment. Through this article, the author intends to investigate the existence and value of women in the ancient times, in the cultures of Israel, Greece, and Rome, which represent the portrait of women before the time of Christ, and also the portrait of women in the narrative in the Gospel of John. For this reason, the author will utilize historical records and archaeology, in addition to, of course, the narrative of the role of women in the Gospel of John. The result of the study shows that women in ancient Jewish, Greek, and Roman cultures were viewed as inferior to men. In contrast, the Gospel of John presented Jesus as a transformer for women, who emancipated and placed them in the same position as Jesus' male disciples, with the same eligibility to be taught and to preach the gospel.Abstrak. Penulis menyoroti bahwa masih banyak terjadi perlakuan diskriminatif terhadap perempuan, bahkan di lingkungan gereja. Melalui tulisan ini penulis ingin menyelidiki eksistensi dan nilai perempuan di masa lampau, dalam budaya Israel, Yunani, Romawi, yang merepresentasikan potret perempuan sebelum masa Kristus, dan juga potret perempuan dalam narasi di Injil Yohanes. Untuk itu penulis akan memanfaatkan catatan-catatan dan arkeologi sejarah, selain tentu saja, juga narasi kiprah para perempuan di Injil Yohanes. Hasil penelitian menunjukkan bahwa perempuan dalam kultur kuno Yahudi, Yunani, dan Romawi dipandang lebih rendah daripada laki-laki. Kontras dengan itu, Injil Yohanes menampilkan Yesus sebagai transformator bagi para perempuan, yang mengangkat dan meletakkan mereka di posisi yang sama dengan para murid Yesus yang pria, dengan kelayakan yang sama untuk diajar dan memberitakan Injil.